The Effect of Institutional Ownership, Financial Performance, and Sustainability Report on Firm Value in Basic Materials Sector Companies - Miftakhul Hanifah Sarjiyono; Januar Eko Prasetio (AIBPM Publisher, 2025)
Business activities in the basic materials sector significantly impact stakeholders, making information transparency a key strategy to enhance investor perception and company valuation. This study aims to analyze the effect of institutional ownership (INST), financial performance (ROA), and sustainability report disclosure (SRDi) on firm value, measured by Price to Book Value (PBV). Data were collected from annual and sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023 using purposive sampling, resulting in 62 companies and 148 usable observations after outlier removal. The results show that only financial performance significantly affects firm value, with a significance value of 0.000 ( 0.05), while institutional ownership (sig. = 0.299) and sustainability report disclosure (sig. = 0.798) have no significant effect. Simultaneous testing also confirms a significant joint influence (sig. = 0.000), although the adjusted R-squared value is only 0.129 (12.9%), indicating that the independent variables collectively explain a limited portion of firm value. These findings suggest that investors in this sector prioritize financial over non-financial information. Future research is recommended to incorporate a broader set of variables or methodologies to better capture the complexity of factors influencing firm value in the basic materials industry